High rate tests of the photon detection system for the LHCb RICH Upgrade - Blago, Michele Piero; Keizer, Floris (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2017)
The photon detection system for the LHCb RICH Upgrade consists of an array of multianode photomultiplier tubes (MaPMTs) read out by custom-built modular electronics. The behaviour of the whole chain was studied at CERN using a pulsed laser. Threshold scans were performed in order to study the MaPMT pulse-height spectra at high event rates and different photon intensities. The results show a reduction in photon detection efficiency at 900V bias voltage, marked by a 20% decrease in the single-photon peak height, when increasing the event rate from 100kHz to 20MHz. This reduction was not observed at 1000V bias voltage.
Gesehen am 22.08.2018